THE LEGAL AND POLITICAL ROLE OF POPULAR REFORMIST MOVEMENTS IN THE FORMATION OF THE BUKHARA PEOPLE’S SOVIET REPUBLIC (1920–1924) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the legal and political role of popular reformist movements primarily the Jadids and Young Bukharans in the formation of the Bukhara People’s Soviet Republic (BXSR) from 1920 to 1924. Drawing on primary constitutional texts, treaties, and archival materials, the study analyzes how these indigenous actors shaped the republic’s legal foundations, promoted secular modernization, and navigated Soviet ideological influence. While Soviet support was decisive, the BXSR bore clear imprints of Muslim reformist ideals, making it a unique case of transitional sovereignty in Soviet Central Asia.